A feminist information engagement framework for gynecological cancer patients. Issue 4 (13th July 2015) - Westbrook, Lynn; Fourie, Ina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a three-part framework of information engagement for situated gynecological cancers. These particular cancers intertwine with medicalization of sexuality and gender power dynamics, situating information behaviors and interactions in women's socio-health perceptions. Using Kavanagh and Broom's feminist risk framework, the framework establishes functional and temporal parameters for sense-making and information engagement. Design/methodology/approach – This paper employs a structured, reiterative literature review with emergent thematic analysis. Nine indices from medicine, information studies, and sociology were searched using combinations of five terms on cervical cancer (CC) and 14 terms on information engagement in the title, abstract, and subject fields. Results were examined on a reiterative basis to identify emergent themes pertaining to knowledge development and information interactions. Findings – Environmentally, social stigma and gender roles inhibit information seeking; normalizing CC helps integrate medical, moral, and sexual information. Internally, living with the dichotomy between "having" a body and "being" a body requires high-trust information resources that are presented gradually. Actively, choosing to make or cede medical decision-making requires personally relevant information delivered in the form of concrete facts and explanations. Research limitations/implications – The study covers only one country. Originality/value – This study's information framework and suggestions for future research encourage consideration of gender power dynamics, medicalization of sexuality, and autonomy in women's health information interactions.